Stereotyping as the Trigger Factor of Discrimination in Ghost Boys by Jewell Parker Rhodes - Elma Sukma Nugraha; Siti Hafsah (Prologue: Journal on Language and Literature, 2023)
This research aims to analyse stereotyping as the trigger factor of discrimination in the novel Ghost Boys by Jewell Parker Rhodes. There are two objective of this research; to find out the categories of stereotype and to explain stereotype trigger discrimination. The theory used in this research is categories of stereotype by David Schneider. The type of research is descriptive qualitative study. The primary data in this research is the novel Ghost Boys by Jewell Parker Rhodes. The result of the research is the researcher found that the categories of stereotypes in the novel Ghost Boys by Jewell Parker Rhodes are; gender, race, age, physical features, occupation, and social economic, and language with 38 data. The most dominant data is racial stereotype as much as 50%. Stereotyping trigger discrimination in the form; of verbal expression, avoidance, exclusion, and physical abuse with 25 data, the most dominant is physical abuse as much as 36%.